Unveiling the high regioselectivity and stereoselectivity within the synthesis of spirooxindolenitropyrrolidine: A molecular electron density theory perspective. (28th January 2021) - Acharjee, Nivedita; Mohammad‐Salim, Haydar A.; Chakraborty, Mrinmoy; Rao, Madhuri P.; Ganesh, Madhu
Abstract: A molecular electron density theory (MEDT) study for the [3 + 2] cycloaddition (32CA) reaction of indoledione and N ‐methyl glycine with ( E )‐1‐bromonitrostyrene leading to the spirooxindole‐pyrrolidine adduct is presented. Electron localisation function (ELF) study of the in situ generated azomethine ylide classifies a pseudodiradical electronic structure associated with low activation energies. This 32CA reaction is a polar process with electronic flux from the strongly nucleophilic azomethine ylide to the strongly electrophilic nitrostyrene, confirmed from the global electron density transfer (GEDT) above 0.20 e at the transition states (TSs). Parr function analysis predicts the correct regioselectivity from the two‐centre interactions. The reaction is kinetically controlled with negative free energy of reaction which makes it irreversible. The activation enthalpy of the favoured TS is lowered by 3.4, 6.3 and 9.3 kcal mol −1 in methanol relative to the other feasible reaction paths, consistent with the experimentally observed complete regioselectivity and stereoselectivity. ELF topological characterisation along the reaction path predicts a two‐stage one‐step molecular mechanism, and bond formation is controlled by the nucleophilic character of the azomethine ylide. ELF study, Laplacian of electron density and independent gradient model (IGM) analysis predict non‐covalent interactions at the TSs, where the new C–C bond formation has not been started. Abstract : The [3 + 2] cycloaddition (32CA) reaction of indoledione and N ‐methyl glycine with ( E )‐1‐bromonitrostyrene is a polar process with electronic flux from the strongly nucleophilic azomethine ylide to the strongly electrophilic nitrostyrene. Highly regioselective and stereoselective formation of the spirooxindolenitropyrrolidine is predicted in agreement with the experiments. This MEDT study allows predicting a two‐stage one‐step molecular mechanism, and bond formation is controlled by the nucleophilic character of the azomethine ylide.